2021
DOI: 10.1155/2021/8886050
|View full text |Cite
|
Sign up to set email alerts
|

A New Mathematical Model for Controlling Tumor Growth Based on Microenvironment Acidity and Oxygen Concentration

Abstract: Hypoxia and the pH level of the tumor microenvironment have a great impact on the treatment of tumors. Here, the tumor growth is controlled by regulating the oxygen concentration and the acidity of the tumor microenvironment by introducing a two-dimensional multiscale cellular automata model of avascular tumor growth. The spatiotemporal evolution of tumor growth and metabolic variations is modeled based on biological assumptions, physical structure, states of cells, and transition rules. Each cell is allocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…As adaptation to hypoxia, changes in gene expression affecting cellular and physiological functions often result in increased cancer aggressiveness and treatment resistance [ 650 , 651 , 652 ]. A recent study using in silico modeling and the simulation of in vivo cancer cell growth found that increasing oxygen concentration and pH value in the TME could result in significant shrinkage of tumor growth size [ 653 ]. Melatonin is an effective oncostatic agent capable of modulating important elements in TME that drive immunosuppression, cell proliferation, metastasis, and resistance to apoptosis [ 654 ].…”
Section: Melatonin May Promote Prp Physiological Functions and Inhibi...mentioning
confidence: 99%
“…As adaptation to hypoxia, changes in gene expression affecting cellular and physiological functions often result in increased cancer aggressiveness and treatment resistance [ 650 , 651 , 652 ]. A recent study using in silico modeling and the simulation of in vivo cancer cell growth found that increasing oxygen concentration and pH value in the TME could result in significant shrinkage of tumor growth size [ 653 ]. Melatonin is an effective oncostatic agent capable of modulating important elements in TME that drive immunosuppression, cell proliferation, metastasis, and resistance to apoptosis [ 654 ].…”
Section: Melatonin May Promote Prp Physiological Functions and Inhibi...mentioning
confidence: 99%
“…It is difficult to experimentally access all the states precisely, especially those existing on shorter time scales, which is why the use of computational models is a real asset. Several models have explored possible states of tumor metabolism and the environment [ 79 , 80 , 81 , 82 , 83 , 84 ]. A recent model [ 85 ], addressed the issue using statistical approaches by attempting to characterize metabolic attractors and their transition zones.…”
Section: Metabolic Landscapementioning
confidence: 99%
“…As an example, Ansarizadeh et al [ 8 ] suggest a complex model, which describes the interaction among normal, immune and tumor cells in a tumor with a chemotherapeutic drug, using a set of coupled PDEs. Moreover, there are approaches such as that in [ 9 ], designed by Pourhasanzade et al, which even look into the microenvironmental factors, as well as at separate types of nutrients and various cell groups of a tumor. These types of models appear to be more detailed and sophisticated PDE sets.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from Table 1 , different models have been developed for the prediction of tumor growth, considering the effects of different factors employing a range of assumptions. For example, many studies consider a single type of generic tumor cells [ 3 , 4 , 5 , 8 , 10 , 11 , 12 , 13 , 14 , 15 ], while others consider separate proliferating, quiescent and necrotic cells within the tumor [ 6 , 7 , 9 , 16 , 17 , 18 ]. The benefit of considering these separate types of cells is a full understanding of intra-tumoral interactions, which prove to be more realistic than a generalized approach.…”
Section: Introductionmentioning
confidence: 99%